Integrating Worship Philosophy into Urban Mission: Motivating the CMC Church Congregation through Worship Education - Ming, David; Budiatmaja, Rudy; Lamsir, Seno (Journal of Asian Orientation in Theology, 2026)
This study explores the integration of the philosophy of worship within Christian religious education in the church, emphasizing its role as a holistic expression of missional service in urban communities. The primary objective is to demonstrate that worship philosophy—when aligned with mission-oriented and pastorally focused teaching—embodies a comprehensive devotion of believers to God. This devotion is expressed through both worship and acts of service that exemplify Christian values, particularly within the complexities of urban life. Drawing on qualitative analysis of various literature sources, the study investigates how mission-oriented pastoral practices have been implemented in urban contexts, where congregational engagement is often hindered by fast-paced lifestyles and spiritual apathy. Despite these challenges, the research finds that many individuals have been effectively encouraged to re-engage with church life through intentional, spiritually grounded approaches that affirm God as the ultimate source of meaning and direction. The findings highlight that contextually sensitive mission services—especially those that are responsive and pastoral in nature—function as redemptive teaching tools. These approaches reawaken inactive congregants and foster renewed commitment to corporate worship. The study concludes that strategic pastoral outreach and mission care in urban settings can effectively revitalize worship participation and empower believers to live faith-filled, victorious lives